PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN BERBASIS ONLINE DENGAN MODUS GIVEAWAY DI PLATFORM MEDIA SOSIAL - Tiara Rahmawati; H. Agus Takariawan; Rully Herdita Ramadhani (Paulus Law Journal, 2022)
The development of the digital era, especially in the technological aspect, has led to various innovations in the field of financial services, one of them is Financial Technology. The type of Financial Technology that is in huge demand and often used is Financial Technology Lending or information technology-based on lending and borrowing services or also known as online loans. Nowadays, Financial Technology Lending used as an alternative investment and practical source of funding for the community. However, along with developments, the convenience provided by Financial Technology Lending services can pose a risk of a criminal act, especially in the cyber aspect. Although in the practice law enforcement related to criminal acts committed within the scope of illegal online loan has been carried out. In reality illegal online loans are still rife in the community. This study aims to examine law enforcement and obstacles related to law enforcement against criminal acts committed within the scope of illegal online loans in Indonesia. By using a normative juridical approach, secondary data sources will be analyzed qualitatively, the following research results are obtained: (1) A description of the factors that affects law enforcement has been applied in tackling criminal acts committed within the scope of illegal online loans; (2) Even though law enforcement has been carried out, in practice there are still obstacles that not being able to eradicate criminal acts that occur within the scope of illegal online loans.